PENGEMBANGAN KEILMUAN; LITERASI AKADEMIK; GURU SEBAGAI PEMBELAJAR SEPANJANG HAYAT - Fahmi; Ayu Wulandari; Riska Julianti Amanda; Sipriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the development of teacher knowledge through academic literacy and the concept of teachers as lifelong learners in improving the quality of education. The method used is library research, analyzing various relevant scientific sources from journals, books, and educational policy documents. The results of the study indicate that teacher knowledge development is a crucial factor in building educational professionalism, particularly in addressing developments in science and technology. Academic literacy serves as the foundation for teachers' ability to critically understand, analyze, and develop knowledge, thereby enabling them to create innovative learning. Furthermore, the concept of teachers as lifelong learners emphasizes that the process of competency development does not stop with formal education but continues through collaboration, reflection, and the use of technology. Despite various challenges such as workload and limited institutional support, teachers' commitment to continuous learning is key to improving the quality of education. Therefore, the integration of academic literacy and lifelong learning is crucial in creating adaptive and competent professional teachers in the modern era.